UniMAP’s E-vehicles services - Allinie Mirna Abdul Malek (Universiti Malaysia Perlis, 2008)
UniMAP’s e-vehicle services is a system that provides vehicles booking services for Universiti Malaysia Perlis’s (UniMAP) staffs and students. By implementing UniMAP’s e-vehicle services, the objectives of this project which are to assist the UniMAP’s Development Department in making the vehicles booking system more systematic and easy to handle as well as to simplify staffs and students in booking vehicles for University purposes achieved. The manual system that being currently used needing staffs and students to fill up the Vehicles Booking Form. This system is working online and can only be access by all users which are UniMAP’s staffs, vehicle drivers and students along with the Development Department that acts as the administrator. Drivers of UniMAP’s vehicles are responsible on taking the users who made the bookings to destinations required. Users can add, edit or cancel bookings and check booking’s status within 24 hours as monitored by the administrator. This new system is effective as current system needing Development Department staffs to check the booking records before confirming the booking’s status. UniMAP’s e-vehicles services system is build using Macromedia Dreamweaver 8 in PHP language, MySQL database, and Apache server on the Windows platform.